Community awareness of intestinal parasites and the prevalence of infection among community members of rural Abaye Deneba area, Ethiopia - Nyantekyi, Liza (Asian Pacific Tropical Medicine Press, 2014)
OBJECTIVE: To assess the knowledge of Abaye Deneba community members regarding intestinal parasites and prevalence of intestinal parasitic infections. METHODS: Knowledge about intestinal parasites was assessed by administering a questionnaire to 345 randomly selected household heads. Parasitological stool examination of 491 randomly selected individuals was done using the formol ether concentration technique. RESULTS: Knowledge of the Abaye Deneba community about parasitic diseases such as schistosomiasis, amoebiasis, ascariasis and taeniasis was very low. However, 204 (59.3%) members correctly responded that the cause of giardiasis is related to contaminated water and 176 (51.2%) knew how to prevent it. In some cases, respondents did correctly identify causes, symptoms of intestinal parasite infection and ways to prevent it, but they did not accurately link it to the appropriate disease caused by the different intestinal parasite species. Among the 491 stool samples examined, 50.2% of study participants showed infection with at least one intestinal parasite. Schistosoma mansoni was the most prevalent (41.3%) followed by Trichuris trichiura(9.4%), Ascaris lumbricoides (8.4%), Taenia saginata (2.4%), Enterobius vermicularis (2.0%) and hookworm (0.4%). Prevalence of schistosomiasis was highest in men aged 15-24 years. CONCLUSIONS: Intestinal parasitic infection is highly prevalent in communities of the Abaye Deneba area. Nevertheless, the knowledge of the community members about the parasite is less. Implementation of preventive chemotherapy, supplemented with health education, provision and use of sanitary facilities would be recommended to reduce morbidity and control transmission of intestinal parasites in this area.